2017
DOI: 10.2147/cia.s134750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of safety and outcomes of shock wave lithotripsy between elderly and non-elderly patients

Abstract: BackgroundThis study compared the clinical outcomes of extracorporeal shock wave lithotripsy between elderly (aged $65 years) and non-elderly (aged <65 years) patients.MethodsA retrospective review of medical records was performed on 483 (non-elderly: 245, elderly: 238) patients with upper urinary tract stones who underwent shock wave lithotripsy between 2007 and 2015. The demographic data, stone parameters, stone-free rate, retreatment rate, and complication rate were analyzed in both elderly and non-elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
3
3
1
Order By: Relevance
“…In a retrospective study of 472 diseases conducted by Gokce et al, no difference was found between age groups and success rates of SWL (6). In a study by Chen et al, the SFR in elderly patients were found similar to that of non-elderly patients (41.1% vs 46.5%) (12). In our study, both SFR and CIRF rate among age groups were similar.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In a retrospective study of 472 diseases conducted by Gokce et al, no difference was found between age groups and success rates of SWL (6). In a study by Chen et al, the SFR in elderly patients were found similar to that of non-elderly patients (41.1% vs 46.5%) (12). In our study, both SFR and CIRF rate among age groups were similar.…”
Section: Discussionsupporting
confidence: 81%
“…The fact that the parameters in the evaluation of treatment success such as different age groups (> 60 years, ≥ 65 years and >/≥ 70 years) definition of success (stone-free, stone-free plus CIRF), definition of CIRF (≤ 2 mm and ≤ 4 mm), time to evaluate success (1 month, 3 months) and evaluation method of treatment result (one or more of KUB graphy, US, CT) are not homogeneous makes it difficult to comment on this issue (6, 8, 10, 12-15). Chen et al found that the rate of retreatment in elderly patients who received SWL for kidney stones was similar to that of non-elderly patients (38.6% vs 42.9%, p = 0.485) (12). In our study, this rate was 27.2% and there was no statistically significant difference between the other age groups.…”
Section: Discussionsupporting
confidence: 63%
“…One study has shown comparable outcomes for ESWL in appropriately selected patients based on stone size and position in those 65 years and older compared with younger patients. 16 In our case series there was a stone-free rate of 68.3%. Other studies evaluating the stone-free rate after ureterorenoscopy in the elderly, which varied from patients over the age of 60 years in some studies to over 70 years in others, found stone-free rates between 65.8% and 97%.…”
Section: Discussionmentioning
confidence: 44%
“…One study has shown comparable outcomes for ESWL in appropriately selected patients based on stone size and position in those 65 years and older compared with younger patients. 16…”
Section: Discussionmentioning
confidence: 99%
“…And the SFR of ESWL for obese patients is also greatly reduced ( 16 ). It is reported that, in comparison with the non-senile group treated by ESWL, there was no significant difference in SFR in senile group ( 17 ). However, the incidence of complications was higher in senile group than that in non-senile group.…”
Section: Discussionmentioning
confidence: 91%